PERBANDINGAN EFISIENSI BANK UMUM SYARIAH GO PUBLIC DAN NON GO PUBLIC PERIODE 2015-2019 - Nugraheni, Alfiyyah (Jurnal Syarikah : Jurnal Ekonomi Islam, 2021)
Initial Public Offering is one the ways for Islamic Bank obtain funds to expand and improve the performance of their companies. However, in practice, Islamic Bank that already have Initial Public Offering have decreased performance compared to before and even lower than Islamic Bank that have not yet gone Initial Public Offering. For the problem, the purpose of this study is to analyze the comparative efficiency of Islamic Bank that already have Initial Public Offering with Islamic Bank have not yet Initial Public Offering. This study uses that DEA method with an intermediation approach for input variables are saving, operational cost, labor cost and output variables are funding and operational income. The result of this study indicate that Islamic Bank Go Public and Non Go Public are quite efficient. Non Go Public Islamic Bank are more efficient that Go Public Islamic Bank but there is no significant difference between the efficiency of Go Public Islamic Bank and Non Go Public Islamic Bank. Key words: Efficiency, DEA, Sharia Bank, Initial Public Offering.